Current Outcomes after Revascularization for Coronary Very Late Stent Thrombosis - Yunqing Hou; Yan Gu; Muli Wu; Yang Zheng; Xinxin Chen; Xiang Wang (Cardiovascular Innovations and Applications)
Objective: Limited data are available regarding current outcomes after revascularization for angiographically confirmed very late stent thrombosis (VLST). Therefore, this study investigated the current outcomes of patients with VLST and the risk factors for major adverse cardiovascular events (MACE). Methods: Consecutive patients who underwent revascularization for angiographically confirmed VLST between January 2014 and January 2016 were enrolled in this study. The patients were divided into two groups according to the occurrence of MACE during follow-up. The clinical and interventional parameters between groups were compared. Results: A total of 564 patients with an average age of 61.61 ± 10.71 years were enrolled. Eight patients died during hospitalization. MACE occurred in 100 patients after a mean follow-up of 620 days. The total MACE rate was 35.46%, and Kaplan-Meier survival analysis indicated an estimated MACE-free survival rate of 22%. Multivariable Cox regression analysis revealed that left ventricular ejection fraction and peak troponin I at VLST onset were independent predictors of MACE. Conclusions: Long-term outcomes after revascularization for VLST remained unfavorable. Left ventricular ejection fraction and peak troponin I at the onset of VLST were independent risk factors for poor prognosis.